Multidisciplinary Team Utilizing Pharmacists in Multimodal, Bundled Care Reduce Chronic Obstructive Pulmonary Disease Hospital Readmission Rates. (February 2021) - Gentene, Anthony J.; Guido, Maria Rose; Woolf, Brittany; Dalhover, Amber; Boesken, Timmi Anne; Mueller, Eric W.; Zafar, Muhammad Ahsan
Background: Chronic obstructive pulmonary disease (COPD) is a major contributor of morbidity and mortality in the United States resulting in high hospitalization and readmission rates. For health systems, identifying an effective strategy to reduce COPD readmissions has remained difficult. Multiple COPD care bundles have been developed with varying degrees of success. Bundles that were multidisciplinary and included pharmacists were successful in reducing readmissions. Objective: To describe and assess a multidisciplinary, 5-element, COPD care bundle that was implemented in an academic, urban safety-net hospital to reduce COPD readmissions and the role of pharmacists in bundle implementation. Methods: A multidisciplinary team collaborated to develop a 5-element COPD care bundle that met unmet patient needs. The bundle elements included the following, with pharmacy responsible for the first two: optimization of COPD inhalers, 30-day supply of insurance-compatible inhalers, individualized patient inhaler teaching, provision of standardized discharge instructions, and scheduling of a 15-day discharge follow-up appointment. Bundle was implemented with multiple Plan-Do-Study-Act (PDSA) cycles to develop intra- and interdepartment processes. Results: Prior to bundle implementation, the health system COPD readmission rates were 22.7%. Reliable implementation of the bundle reduced readmissions to 14.7% over a 6-month period. Pharmacy adherence to completion of the bundle was over 95% over 2 years of bundle use. Conclusion: Pharmacists have a crucial role in hospital-based transitions of care to reduce COPD readmissions.